Carbon Stocks on Forest Stewardship Program and Adjacent Lands - Nilesh Timilsina; Francisco J. Escobedo; Alison E. Adams; Damian C. Adams (EDIS)
Nonindustrial private forestlands in Florida provide many environmental benefits, or ecosystem services. Ecosystem services are benefits from nature that are directly enjoyed, consumed, or used by humans, such as water quality improvement or protection, recreation, biodiversity, and even timber. Another benefit from forests that is gaining interest is their ability to store carbon through the photosynthetic capture of carbon dioxide, a greenhouse gas, in tree, plant, and soil biomass. The carbon dioxide that is stored over the life of a forest, called carbon stocks, is not only important for mitigating greenhouse gas contributions to climate change, but it can also be valued in several markets and incorporated into environmental policy instruments. This 5-page fact sheet was written by Nilesh Timilsina, Francisco J. Escobedo, Alison E. Adams, and Damian C. Adams and published by the UF Department of School of Forest Resources and Conservation April 2017.